SHAME AS AN EXPERIENCE OF LACK: TOWARD A NEW PHENOMENOLOGICAL APPROACH TO SHAME - Raba, Martin (Problemos, 2017)
The purpose of this paper is to give a sketch of a new phenomenological approach to shame. I claim that prevailing theories of shame are too narrow and reduce shame to a mere fear of social sanctions or to an intimate experience wherein a subject becomes an object of external social norms. Instead, I demonstrate that we should understand shame as an experience wherein an individual feels his incapability of meeting the standards of the ego-ideal, since he lacks something valuable. From this perspective shame is, on the one hand, a profoundly intimate experience wherein an individual evaluates herself negatively because she lacks something she thinks she requires. On the other hand, since lack reveals itself only through a process wherein an individual compares her real self to the ego-ideal, shame always has an ideological dimension since the ego-ideal reflects the shared ideological values an individual is attached to and constitute part of one’s self-conception.
Keywords: shame; ideology; J-P Sartre; ego-ideal; phenomenology of the self